Cross-species genetic screens to identify kinase targets for APP reduction in Alzheimer's disease. (12th February 2019) - Huichalaf, Claudia H; Al-Ramahi, Ismael; Park, Kyung-Won; Grunke, Stacy D; Lu, Nan; de Haro, Maria; El-Zein, Karla; Gallego-Flores, Tatiana; Perez, Alma M; Jung, Sung Yun; Botas, Juan; Zoghbi, Huda Y; et al.
Abstract: An early hallmark of Alzheimer's disease is the accumulation of amyloid-β (Aβ ), inspiring numerous therapeutic strategies targeting this peptide. An alternative approach is to destabilize the amyloid beta precursor protein (APP) from which Aβ is derived. We interrogated innate pathways governing APP stability using a siRNA screen for modifiers whose own reduction diminished APP in human cell lines and transgenic Drosophila. As proof of principle, we validated PKCβ —a known modifier identified by the screen—in an APP transgenic mouse model. PKCβ was genetically targeted using a novel adeno-associated virus shuttle vector to deliver microRNA-adapted shRNA via intracranial injection. In vivo reduction of PKCβ initially diminished APP and delayed plaque formation. Despite persistent PKCβ suppression, the effect on APP and amyloid diminished over time. Our study advances this approach for mining druggable modifiers of disease-associated proteins, while cautioning that prolonged in vivo validation may be needed to reveal emergent limitations on efficacy.